2023
DOI: 10.1002/alz.13063
|View full text |Cite|
|
Sign up to set email alerts
|

FDA‐approved carbonic anhydrase inhibitors reduce amyloid β pathology and improve cognition, by ameliorating cerebrovascular health and glial fitness

Abstract: IntroductionCerebrovascular pathology is an early and causal hallmark of Alzheimer's disease (AD), in need of effective therapies.MethodsBased on the success of our previous in vitro studies, we tested for the first time in a model of AD and cerebral amyloid angiopathy (CAA), the carbonic anhydrase inhibitors (CAIs) methazolamide and acetazolamide, Food and Drug Administration–approved against glaucoma and high‐altitude sickness.ResultsBoth CAIs reduced cerebral, vascular, and glial amyloid beta (Aβ) accumulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 143 publications
0
23
0
Order By: Relevance
“…More recently, an overexpression of the mitochondrial isoform CA VB was reported in human post mortem brain samples from AD patients presenting cerebral amyloid angiopathy. Such an increase was also reported in the brains of TgSWDI mice, a well-known transgenic AD model Figure ) and methazolamide ( MTZ , Figure ), prevented amyloid-β peptide (Aβ)-mediated apoptosis in neuronal, brain microvascular endothelial, and vascular smooth muscle cells by impeding different mitochondria-mediated proapoptotic mechanisms, such as CytC release, loss of the mitochondrial membrane potential, and production of mitochondrial ROS. The same compounds protected against cerebrovascular pathology and cognitive impairments observed TgSWDI mice.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…More recently, an overexpression of the mitochondrial isoform CA VB was reported in human post mortem brain samples from AD patients presenting cerebral amyloid angiopathy. Such an increase was also reported in the brains of TgSWDI mice, a well-known transgenic AD model Figure ) and methazolamide ( MTZ , Figure ), prevented amyloid-β peptide (Aβ)-mediated apoptosis in neuronal, brain microvascular endothelial, and vascular smooth muscle cells by impeding different mitochondria-mediated proapoptotic mechanisms, such as CytC release, loss of the mitochondrial membrane potential, and production of mitochondrial ROS. The same compounds protected against cerebrovascular pathology and cognitive impairments observed TgSWDI mice.…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, chronic treatment with CAIs reduced Aβ burden in neuronal, vascular, and glial cells, decreased Aβ-driven caspase-3 activation in endothelial cells in microglia, astrocytes, and endothelial and smooth muscle cells, and prevented glial overactivation. These inhibitors also showed important effects on modulating cerebral blood flow, alleviating microvessel constriction, and reducing microhemorrhages. ,, All of these mechanisms suggest potential effectiveness for AD therapy. However, no study accessed the effects of CAIs on clinics.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…24 Together with the well-known roles of AChE and butyrylcholinesterase (BChE) enzymes at the AD, it has also been shown that CA inhibitors reduce amyloid β pathology and improve cognition by ameliorating cerebrovascular health and glial fitness. 25 Studies have demonstrated that CA inhibitors such as acetazolamide (AZA) and methazolamide (MTZ) mitigate mitochondrial dysfunction and apoptosis triggered by amyloid β in both vascular and neural cells. This effect is achieved by diminishing the production of reactive oxygen species (ROS) within the mitochondria and preventing the decline of mitochondrial membrane potential.…”
Section: Introductionmentioning
confidence: 99%